2020
DOI: 10.1177/1178646920970902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sleep Deprivation on the Tryptophan Metabolism

Abstract: Sleep has a regulatory role in maintaining metabolic homeostasis and cellular functions. Inadequate sleep time and sleep disorders have become more prevalent in the modern lifestyle. Fragmentation of sleep pattern alters critical intracellular second messengers and neurotransmitters which have key functions in brain development and behavioral functions. Tryptophan metabolism has also been found to get altered in SD and it is linked to various neurodegenerative diseases. The kynurenine pathway is a major regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 142 publications
2
33
0
Order By: Relevance
“…SD is one of the major risk factors that impair learning and memory. Adverse changes in cognitive performance have been associated with total and partial SD [6]. In the present study, fish exposed to extended light phase and light pulses showed decreased locomotor strength in partition preference and spinning task and increased working errors in T-maze tests, signifying the induction of SD.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…SD is one of the major risk factors that impair learning and memory. Adverse changes in cognitive performance have been associated with total and partial SD [6]. In the present study, fish exposed to extended light phase and light pulses showed decreased locomotor strength in partition preference and spinning task and increased working errors in T-maze tests, signifying the induction of SD.…”
Section: Discussionsupporting
confidence: 51%
“…Normal sleeping pattern induces long term potentiation (LTP), synaptic plasticity and promotes memory formation [5]. Sleep Deprivation (SD) is reduction in sleeping time below the baseline requirement [6] which is reported to cause learning and memory deficits [7]. Although the exact pathogenetic mechanism of action of SD on memory impairment remains elusive, over activation of microglial cells and increased nuclear factor (NF-κB) in turn levels of proinflammatory cytokines such as Interleukin 1 beta (IL-1β), Interleukin 6 (IL6), tumor necrosis factor alpha (TNF-α) are reported as crucial factors [8].…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia is known to cause disorders in tryptophan metabolism (Bhat et al. 2020 ). It can be seen from the results of differential metabolites that the tryptamine in the PCPA group was significantly reduced, while the N -γ-acetyl- N -2-formyl-5-methoxykynurenamine (AFMK), as the enzymatic degradation production of 5-HT, was elevated.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is intriguing that the effect was obtained with a total of only 7–9 min of high-intensity exercise per week. Furthermore, the effect seems robust in that it was statistically significant with the limited number of individuals included in the study and without full control of diet and sleep, factors that can affect the concentration of KP metabolites [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%